Politics of Dissent - Jørgensen, Martin Bak 1973- (Political and Social Change, 2015)
There are alternatives to neoliberal market economies: basic income, the money of the common and degrowth. This study highlights the potential of dissent from the initial questioning of the dominant system to the creation of new political agendas. It discusses the multiple manifestations of dissent and their contributions to shaping political alternatives; it also takes a closer look at organizations and the challenge they face trying to establish forms of resistance. The struggles of current social movements in Brazil, Turkey, Nigeria, Spain and the US exemplify practices of dissent